E-Tribes: um estudo do comportamento dos consumidores à luz da Teoria das Representações Sociais - Moraes, Thiago Assunção de (2013)
The initiative to create a virtual community has given to Brands the possibility of approaching the consumer and understands how the interactions occur between them, to the point of creating a grupal identity and a commitment in the light of experiences. However, the creation does not guarantee that consumers will be willing to have these same experiences with the brand and its products, but will make noticeable a standardization of behavior that leads to consume, based on cultural dimensions that involve local, rituals, artifacts, affection and shared awareness, giving rise to a tribe of consumption. Thus, to analyze the process that takes a virtual community of consumption to behave as a tribe, this study appropriated qualitative procedures to capture individuals' speech patterns, obtained by the use of netnography, reflecting the sense of e-tribe. These individuals were selected from the intensity of their interactions in the virtual community chosen, defined as Insiders and Devotees, where, in Social Representations Theory, the process of Anchoring generated their collective opinion, giving rise Discourses of Collective Subject to that evidenced in peladeiro.com.br community, a tribe behavior depending on the peladas (informal soccer games) and not exactly the brand sponsor of the virtual community. The data were analyzed by analysis of collective opinion with the help of software Qualiquantisoft, which allowed the generation of anchors forming DCS s (Discourses of Collective Subject) who responded to the research objectives. The results generates to the academic and managerial environments another approach in studies of virtual brand communities and the opportunity to understand the relationship of tribe that involves consumption and consumers so that these perspectives bring knowledge in marketing that provide balance in the exchange system . The study brings in its findings the elements found in the social relations of a virtual community that make this community a tribe. The limitations of the study that are offered at the end of work, can be seen as opportunities to expand knowledge both in the field of Marketing Theory as involved.